Division of Dairy Extension National Dairy Research Institute, Karnal-132 001, Haryana - PONNUSAMY, K. (Annals of Agricultural Research, 2014)
The present study envisaged to asses and analyse the various constraints of individual farm enterprises and integrated farming system as a whole in the coastal Tamil Nadu during 2005. The ranking was done by the farmers based on the importance or severity of the problems in 8 coastal villages. Marketing, input natural calamities in crop production ; low milk price, diseases, decreasing common grazing land in livestock production ; disease and predators in poultry and lack of government support, wide price fluctuations in fisheries were ranked by farmers as major problems in individual enterprises. The major constraints in adopting integrated farming system were found to be heavy investment in the initial stage, lack of marketing for the produces from different enterprises, labour unavailability and its high cost and lack of infrastructure in addition to scattered land holdings of farmers.